2001
DOI: 10.1103/physrevlett.87.015504
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Energy Relaxation and Transition Frequency Jumps of Single Molecules at 30 mK

Abstract: Transition frequency jumps for single terrylene molecules in a polyethylene matrix caused by resonant laser irradiation are investigated at 30 mK. These jumps are not accompanied by substantial sample heating. A model for the effect is proposed, based on the interaction of tunneling two-level systems (TLSs) surrounding the single molecule with high-energy nonthermal phonons emitted by the molecule during electronic energy relaxation. The radius of the effective interaction volume is estimated to be r m ഠ 12.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The individual probabilities, P n ͑͒ can be provided by a microscopic model for SD. 26 In Figs. 2͑a͒ and 2͑b͒ we plot the spectral jump histograms obtained from two single NCs with R ϳ 2.5 nm and R ϳ 4 nm cores, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…The individual probabilities, P n ͑͒ can be provided by a microscopic model for SD. 26 In Figs. 2͑a͒ and 2͑b͒ we plot the spectral jump histograms obtained from two single NCs with R ϳ 2.5 nm and R ϳ 4 nm cores, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…[26,27] Most studies have so far been concerned with probing local dynamics of the host at cryogenic temperatures. [28][29][30][31][32] In 2006, Butter et al reported on the orientation of single terrylene molecules in PE. [33] We have studied drawn PE films at the single-molecule level in order to determine the distribution of the orientations of individual, embedded chromophores and its dependence on stretching.…”
Section: Introductionmentioning
confidence: 99%